Current Concepts on 6-sulfo LacNAc Expressing Monocytes (slanMo) - Ahmad, Fareed; Döbel, Thomas; Schmitz, Marc; Schäkel, Knut (Frontiers in Immunology, 2019)
The human mononuclear phagocyte system consists of dendritic cells (DCs), monocytes and macrophages having different functions in bridging innate and adaptive immunity. Among the heterogeneous population of monocytes the cell surface marker slan (6-sulfo LacNAc) identifies a specific subset of human CD14- CD16+ non-classical monocytes, called slan+ monocytes (slanMo). In this review we discuss the identity and functions of slanMo, their contributions to immune surveillance by proinflammatory cytokine production, and cross talk with T cells and NK cells. We also consider the role of slanMo in the regulation of chronic inflammatory diseases and cancer. Finally, we highlight unresolved questions that should be the focus of future research.